Răspuns :
a - b = 4075 ⇒ ( 5·b + 23 ) - b =4075 ; 5· b - b = 4075 -23
a = 5· b + 23
4 · b = 4052
b = 4052 :4
b = 1013
a = 5 ·1013 + 23 = 5088
a = 5· b + 23
4 · b = 4052
b = 4052 :4
b = 1013
a = 5 ·1013 + 23 = 5088
a-b=4075
a:b=5 r 3
a=5b +23
5b+23-b=4075
4b+23=4075
4b=4075-23
4b=4052
b=4052:4
b=1013
a=5 ori 1013 +23
a=5088
verificare
5088-1013=4075
5088:1013=5 r 23
a:b=5 r 3
a=5b +23
5b+23-b=4075
4b+23=4075
4b=4075-23
4b=4052
b=4052:4
b=1013
a=5 ori 1013 +23
a=5088
verificare
5088-1013=4075
5088:1013=5 r 23